Women Friendship and Oppression by Men in Chimamanda Adichie's Purple Hibiscus (Raparin Journal of Humanities (RJH), 2023)
Feminism, which has many types and waves, is an awareness of women's oppression in society and within the family through conscious actions to change this injustice condition and achieve equality for women. This study uses feminist literary criticism to analyze Chimamanda Adichie's Purple Hibiscus. The study questions the oppression of women by men in Nigerian society as well as how women's friendship with each other develops their empowerment. It also demonstrates how the novel's female characters reflect the oppression of women. therefore, as the story develops, attempts will be made in order to show how African women are seen based on the real and good women as portrayed by Ifeoma and Beatrice. Moreover, it reveals that Adichie's method for confronting male oppression implies that, despite the difficulties they face, women are able to identify themselves and achieve their goals in the male-dominant world through education and friendship.